PENGARUH VARIASI SUSUNAN PIPA TERHADAP LAJU PELEPASAN KALOR PADA KOLEKTOR SURYA ABSORBER BATU GRANIT - Mirmanto, Mirmanto; Wirawan, Made; Tira, Hendry Sakke (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2015)
As the fossil energy gradually gets depletion, alternative energies should be utilized.  One of alternative energies, which is easier to be used, is solar energy. In this research, the solar energy, which was captured using a flat plate collector with a granite absorber, was used to heat water. The overall dimension of the collector was 0,8 m x 1 m x 0,01 m with a gap between the glas cover and the absorber of approximately 50 mm. Copper pipes with a diameter of 1/2 inch were used to transfer the heat to the water. The volumetric rates of the water were 200 cc / min, 250 cc / min and 300 cc / min and the water was flowed naturally from a higher water tank and was adjusted using a valve installed at the outlet of the collector.The test results indicate that the energy absorbed by the water decreases with the observation time. The parallel pipes cause quick heat removals from the granite absorber. Energy absorbed by the water in the parallel pipes is much greater than that in the serpentine pipe, and the granite can be used for storing the heat energy